Family history and recurrence of febrile seizures. Issue 5 (May 1994) - van Esch, A; Steyerberg, E W; Berger, M Y; Offringa, M; Derksen-Lubsen, G; Habbema, J D
Abstract : To determine the value of a detailed family history for the assessment of the risk of recurrence of febrile seizures, 115 children who visited the emergency room of an academic children's hospital were studied prospectively. The recurrence risk of febrile seizures was analysed in relation to the child's family history and the proportion of relatives affected by febrile seizures using Kaplan-Meier estimates and Cox proportional hazard models. A first degree family history positive for febrile seizures (parents or siblings affected by febrile seizures) increased a child's two year recurrence risk from 27 to 52%. No significant increase of recurrence risk for febrile seizures was found in children with second degree relatives (grandparents and uncles/aunts) or cousins only affected by febrile seizures. Recurrence risk was significantly correlated with the proportion of first degree relatives affected by febrile seizures: risks were 27, 40, and 83% in children whose proportion was 0, 0-0.5, and > or = 0.5 respectively. Analysis of the recurrence risk in relation to a weighted proportion, adjusted for the attained age and sex of first degree relatives, showed similar results. It is concluded that the application of the proportion of first degree relatives affected by febrile seizures generates a more differentiated assessment of the recurrence risk of febrile seizures.